Desain dan Simulasi Kontrol Elektropneumatik Pada Mesin Sealer Cup Semi Otomatis - Agnes Sholikhah; Ardit Mauladana; Ahmad Navis Hidayat; M Alfa Reza; Edy Setiawan (Joule (Journal of Electrical Engineering), 2025)
Pneumatics has advantages in terms of response speed, cleanliness, and ease of maintenance, making it suitable for application in small to medium-scale automation systems. This study aims to design and simulate a semi-automatic cup sealing machine based on a pneumatic system using a cascade control logic approach. The background of this research is based on the increasing demand from the beverage packaging industry for efficient and partially automated cup sealing systems to enhance productivity. The methods employed include system analysis, formulation of control logic in the form of Boolean equations, and grouping of actuator work sequences using the cascade method to ensure a systematic and structured workflow. The system consists of three pneumatic actuators (pistons A, B, and C), a position sensor, a timer, and a 5/2-way two-position five-port pneumatic valve suitable for a two-channel system. Simulation and performance validation of the system were conducted using FluidSim software. Simulation results show that all components operate according to the designed sequence, with synchronised and timely actuator movements without logic conflicts. The implementation of cascade logic proved effective in regulating the system's operational sequence in a stable and efficient manner. This study concludes that a cascade logic-based pneumatic control system has the potential to enhance the efficiency of semi-automated systems and can be further developed towards full automation in industrial applications.